Analysis Of Sustainability Report Disclosures Based On Financial Performance at PT Jamkrindo - Alhaniyah Nurshabrina; Etty Gurendrawati; Indah Muliasari (Research Trend in Technology and Management, 2024)
This research aims to analyze financial performance using profitability, solvency and liquidity ratios as well as analyzing the disclosure of the Sustainability Report which consists of economic, environmental and social aspects at PT Jamkrindo for the 2019-2021 period. The method used in this research is descriptive quantitative with secondary data collection methods. Data analysis techniques are carried out by calculating ratios, creating content analysis techniques in the Sustainability Report, followed by interpreting correlations from financial performance data and PT Jamkrindo's Sustainability Report for 2019-2021. The results of this research show that financial performance in profitability ratios as described by ROA and ROE from 2019-2021 has increased. Meanwhile, the solvency ratio described by DAR and DER as well as the liquidity ratio described by the Current Ratio and Cash Ratio during 2019-2021 experienced an increase in 2020 then decreased in 2021. In the disclosure of PT Jamkrindo's Sustainability Report during 2019-2021 the highest score in 2020 and the lowest score in 2019. In the categories in the special standards, it shows that the economic aspect is more dominant than other aspects. An increase in the Sustainability Report disclosure score indicates a commitment to sustainable practices. Therefore, it can be concluded that there is a link between good financial performance and an increase in PT Jamkrindo's Sustainability Report disclosure score.